What can the brand manager expect from Facebook?. Issue 1 (February 2018) - Sitta, Desislava; Faulkner, Margaret; Stern, Philip
Highlights: We examine the use of Facebook by 100 global brands through two studies. Results challenge the assumptions about the ability of branded Facebook pages to expand and engage users. The most valuable brands are not able to build a correspondingly larger fan base. Recruitment of fans was found to be contingent on industry type. Implications for management of branded pages are discussed. Abstract: Managers cannot afford to ignore social media and have stepped up their involvement in the belief that social media activities extend the brand's reach and engagement with consumers. Facebook is the preeminent social medium with an ever increasing branded content. One hundred brands selected from the Interbrand "Best Global Brand Report" form the basis of this study to test research propositions about the ability of branded Facebook pages to expand and engage users. Data captured from branded Facebook pages was supplemented with socialbaker's data. No correlation is found between the size of a brand and the number of Facebook fans, and there is no consistent relationship with user engagement and brand size. The authors discuss broadening reach, improving engagement, interaction and activity and the implications for social media strategies and make recommendations for managing Facebook presence. Paid advertising is required to increase brand reach to all potential category users. Chinese Abstract: 管理者不能忽视社交媒体, 他们现在更加相信社交媒体活动延伸了品牌影响力以及与消费者的接触. Facebook 是品牌内容不断增加的卓越社交媒体. 从 Interbrand 《最佳全球品牌报告》中选出的一百个品牌构成了本研究的依据, 旨在试验经过品牌塑造的 Facebook 页面在用户扩展和吸引能力方面的相关研究命题. 经过品牌塑造的 Facebook 页面所获取的数据得到 Socialbaker 数据的补充. 在品牌规模与 Facebook 粉丝数量之间没有发现相关性, 而用户参与度和品牌规模之间没有对应关系. 作者探讨了不断扩大的覆盖范围, 不断提升的参与度, 互动和活动以及对社交媒体战略的影响, 并提出管理 Facebook 活动的建议. 需要付费广告扩大对所有潜在用户类别的品牌覆盖.